2012
DOI: 10.1186/1752-153x-6-s2-s6
|View full text |Cite
|
Sign up to set email alerts
|

Common plants as alternative analytical tools to monitor heavy metals in soil

Abstract: BackgroundHerbaceous plants are common vegetal species generally exposed, for a limited period of time, to bioavailable environmental pollutants. Heavy metals contamination is the most common form of environmental pollution. Herbaceous plants have never been used as natural bioindicators of environmental pollution, in particular to monitor the amount of heavy metals in soil. In this study, we aimed at assessing the usefulness of using three herbaceous plants (Plantago major L., Taraxacum officinale L. and Urti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 19 publications
2
48
2
1
Order By: Relevance
“…P. major was examined in terms of heavy metal accumulation in a recent study in the Region of Durrës, Albania, and in Rome, at sites selected according to their different level of anthropogenic pollution, also in connection with the car traffic. Our results for Zn and Pb concentration were much higher, although Cu and Mn contents were lower than the amounts found in the investigations of Malizia et al (2012) and Bekteshi and Bara (2013). In a recent study by Galal and Shehata (2015) on the impact of road traffic pollution on P. major, the plants accumulated more than 10,000 mg kg −1 Fe and Al in the shoots; therefore, it was considered as a hyperaccumulator.…”
Section: Plant Elemental Composition and Element Patternscontrasting
confidence: 78%
“…P. major was examined in terms of heavy metal accumulation in a recent study in the Region of Durrës, Albania, and in Rome, at sites selected according to their different level of anthropogenic pollution, also in connection with the car traffic. Our results for Zn and Pb concentration were much higher, although Cu and Mn contents were lower than the amounts found in the investigations of Malizia et al (2012) and Bekteshi and Bara (2013). In a recent study by Galal and Shehata (2015) on the impact of road traffic pollution on P. major, the plants accumulated more than 10,000 mg kg −1 Fe and Al in the shoots; therefore, it was considered as a hyperaccumulator.…”
Section: Plant Elemental Composition and Element Patternscontrasting
confidence: 78%
“…Bothe [49] presents details about the mechanisms used by plants to tolerate metals, while providing a vast literature. As it is known [45,49] in general, and also in our studies, roots have a higher metal content than the aboveground part of plants, which can be seen in Tables 8, and 9. It was also found that in area A, elements such As, Cr, Mn, and Ni presented higher concentrations in all three plant parts as compared to area B (Tables 8 and 9).…”
Section: Element Concentration In Plantssupporting
confidence: 84%
“…Thus they used a non-destructive method without harvesting the whole plant individual, in order to conclude that these plant species can be bioindicators. They described the evolution of a pollutant over a longer period of time [44,45]. However, many previous studies have revealed the phytotoxic effects of metals translocated from soil to roots and their aboveground parts.…”
Section: Element Concentration In Plantsmentioning
confidence: 99%
“…Close to high-traffi c roads in the center of Rome the concentration of manganese in soil was found to be 546 mg kg -1 and in dandelion growing in this area its concentration was 61 mg kg -1 and 41 mg kg-1 in roots and leaves, respectively (Malizia et al 2012).…”
Section: Loranger Et Al 1994amentioning
confidence: 99%